2020
DOI: 10.1038/s41427-020-00262-z
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of densified silica glass: characterizing the order within disorder

Abstract: The broken symmetry in the atomic-scale ordering of glassy versus crystalline solids leads to a daunting challenge to provide suitable metrics for describing the order within disorder, especially on length scales beyond the nearest neighbor that are characterized by rich structural complexity. Here, we address this challenge for silica, a canonical network-forming glass, by using hot versus cold compression to (i) systematically increase the structural ordering after densification and (ii) prepare two glasses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 50 publications
4
45
0
Order By: Relevance
“…In this section, we review recent structural studies on the structure of glassy, liquid and amorphous materials by diffraction techniques combined with computer simulations aided by topological analyses [4]. Over the last 20 years, we have been working on the structure of disordered materials, oxide glasses [48,53,[56][57][58][59], amorphous oxide materials [60][61][62], chalcogenide fast phase-change materials [63][64][65][66], metallic glasses [67], water [68], high-temperature oxide melt [69][70][71], densified glass [72], and other functional materials [73,74].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we review recent structural studies on the structure of glassy, liquid and amorphous materials by diffraction techniques combined with computer simulations aided by topological analyses [4]. Over the last 20 years, we have been working on the structure of disordered materials, oxide glasses [48,53,[56][57][58][59], amorphous oxide materials [60][61][62], chalcogenide fast phase-change materials [63][64][65][66], metallic glasses [67], water [68], high-temperature oxide melt [69][70][71], densified glass [72], and other functional materials [73,74].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the FSDP of silica glass is related to the formation of a random network, as suggested by Zachariasen [75], and the model was extended to silicate glasses, as illustrated in figure 7 of reference [86], by Mei et al It was confirmed that intermediate-range ordering (IRO) arises from the periodicity of boundaries between successive small cages in the network, formed by connected regular SiO 4 tetrahedra with shared oxygen atoms at the corners. The IRO is thus associated with the formation of a ring structure and cavities [48,72]. The second maximum, the PP, reflects the size of the local-network-forming motif, whereas the FSDP indicates the arrangement of these motifs on an intermediate range, according to Zeidler and Salmon [87].…”
Section: Glassy and Liquid Siomentioning
confidence: 99%
“…This could indicate σ Nd depends on the state of disorder within the network structure. Both, a higher cooling rate as well as higher uniaxial stress, should increase the disorder state of the glass network [58,59]. Data using the σ Nd -parameter as a sensor for cooling rate or uniaxial stress in the elastic regime has not been previously reported.…”
Section: Us(σ Nd ) =mentioning
confidence: 99%
“…The absence of translational periodicity and symmetry, and the rich structural complexity make it difficult to understand the order within disorder 1 , 2 in disordered materials. The advent of advanced instrumentation and measurement protocols makes it feasible to use quantum beam diffraction (X-ray diffraction (XRD) and neutron diffraction (ND)) techniques to reveal the structure of disordered materials at synchrotron and/or neutron sources 3 – 6 .…”
Section: Introductionmentioning
confidence: 99%